Analisis Konsep Triple Bottom Line dalam Program Corporate Social Responsibility di Kampung Berseri Astra Gedangsari - Kusuma, Alan; Fajri, Choirul (Borobudur Communication Review, 2024)
The Corporate Social Responsibility program is an obligation for companies operating in Indonesia. This research focuses on the application of the Triple Bottom Line concept in the Corporate Social Responsibility program implemented by PT Astra International Tbk in Kampung Berseri Astra Gedangsari. Using a descriptive qualitative approach and literature review, this study collects data from various sources, including the company's annual reports and online media, to evaluate the effectiveness of the CSR program, which focuses on social, economic, and environmental aspects. The research findings indicate that this program has successfully improved the quality of life of the local community through initiatives in education, entrepreneurship, health, and environmental preservation.